Fabrication and Characterization of Sansevieria trifasciata, Pandanus amaryllifolius and Cassia angustifolia as Photosensitizer for Dye Sensitized Solar Cells. (April 2016) - Cari,; Supriyanto, Agus; Fadli, Ulfa Mahfudli; Prasada, Ashari Bayu
Abstract: Dye sensitized Solar Cells (DSSC) is one of the electric cells photochemical consisting of photoelectrode, dye, counter electrode, and electrolyte. The aims of the research to determine of the optical and electrical characteristic of the extract Sansevieria trifasciata, Pandanus amaryllifolius, and Cassia angustifolia. The study is also aimed to determine the effect of natural dyes extract to increase the efficiency of solar cells based DSSC. Sandwich structures formed in the sample consisted of working electrode pair Titanium dioxide (TiO2 ) and the counter electrode platinum (Pt). Dye extraction process is performed by stirring for 1 hour and then allowed to stand for 24 hours. Absorbance test is measure by using UV-Vis spectrophotometer Lambda 25, conductivity test by using a two-point probes Elkahfi 100, and characterization of current and voltage (I-V) by using a Keithley 2602A. The results showed that the greatest efficiency of 0.160% at Dye Pandanus amaryllifolius.